2013
DOI: 10.1021/je300997v
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Deep Eutectic Solvents by Phenols and Choline Chloride and Their Physical Properties

Abstract: Novel deep eutectic solvents (DES) based on three different hydrogen-bond donors (HBD), namely phenol, o-cresol, and 2,3-xylenol, and choline chloride (ChCl) were successfully synthesized with different mole ratios of HBD to ChCl. Melting temperature of these DES were measured. Compared with an ideal mixture of the two components, the freezing temperature of the DES depresses greatly from (120 to 127) K. The physical properties, such as density, viscosity, and conductivity of phenol-based and o-cresol-based DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(94 citation statements)
references
References 33 publications
6
87
0
1
Order By: Relevance
“…At 25 °C, the viscosity values of different DESs reported in the literature range from 50 mPa s to 5,000 mPa, for example, viscosity up to 500 mPa · s is reported in the case of the equimolar oxalic acid/choline chloride DES system [23,81,82]. In general, at 25 °C the DES viscosity values are similar to those observed in the case of classical ILs.…”
Section: Viscositysupporting
confidence: 70%
“…At 25 °C, the viscosity values of different DESs reported in the literature range from 50 mPa s to 5,000 mPa, for example, viscosity up to 500 mPa · s is reported in the case of the equimolar oxalic acid/choline chloride DES system [23,81,82]. In general, at 25 °C the DES viscosity values are similar to those observed in the case of classical ILs.…”
Section: Viscositysupporting
confidence: 70%
“…As the covalent bonds were formed, the crystal structure of MnCl 2 Á4H 2 O with acetamide or glycerol collapsed and this could leads towards the lower lattice energies in the DESs [27]. Where in such case, lesser energy is required to break the bonds, resulting in a depression of freezing point when the ion size is larger with smaller ion charges [28].…”
Section: Resultsmentioning
confidence: 99%
“…Where in such case, lesser energy is required to break the bonds, resulting in a depression of freezing point when the ion size is larger with smaller ion charges [28]. Thus, such DES with low lattice energy is the reason for its liquid phase existence at room temperature [27]. These findings are especially interesting as generally, DESs with a freezing point lower than 50 8C are of special demand since they could be at lower cost of production and usage, also as safer solvents in many industries [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pang et al [26] found that choline chloride can react with phenols to form DES, which become a uniform liquid phase to separate phenols from oil. Guo et al [27,28] studied the phenol removal efficiency of choline chloride and its homologous compounds from model oils and then discussed how different cations and anions affect the removal efficiency of phenol. With the upsurge of green chemistry, the utilization of DES is predicted to draw increasing attention.…”
Section: Introductionmentioning
confidence: 99%